2015
DOI: 10.4067/s0718-58392015000200013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of floating covers on gas emissions from liquid pig manure

Abstract: Livestock manure is the source of different pollutant gases that can generate soil acidification, eutrophication, and contribute to global warming, or have a negative impact on health. Covers can control gas emissions from manure, but their impact is still under discussion. The aim of this experiment was to study the effect of different covers on methane (CH4), nitric oxide (NO), hydrogen sulfide (H2S), ammonia (NH3), carbon monoxide (CO), and carbon dioxide (CO2) emissions from liquid pig manure. Six types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The concealing of animal slurry with different material (plastic, straw, saw-dust, etc.) has been identified as an efficient mitigation strategy for the abatement of NH 3 emission [53,54]. Emission reductions for NH 3 , CH 4 , and CO 2 were achieved by −68% (CI −81, −55), −16% (CI −33, 1), and −31% (CI −45, −17) (Figure 4), respectively, while an increase in emission was noticed for N 2 O, by several orders of magnitude (+13502% (CI −25, +39600)).…”
Section: Use Of Covers For Manure Storagementioning
confidence: 99%
“…The concealing of animal slurry with different material (plastic, straw, saw-dust, etc.) has been identified as an efficient mitigation strategy for the abatement of NH 3 emission [53,54]. Emission reductions for NH 3 , CH 4 , and CO 2 were achieved by −68% (CI −81, −55), −16% (CI −33, 1), and −31% (CI −45, −17) (Figure 4), respectively, while an increase in emission was noticed for N 2 O, by several orders of magnitude (+13502% (CI −25, +39600)).…”
Section: Use Of Covers For Manure Storagementioning
confidence: 99%
“…At the stage of storage, an effective way of lowering the GHG emissions from pig slurry is the storage of slurry in hermetically sealed tanks or in tanks equipped with a special covers, e.g. plastic film cover or combinations of lightweight expanded clay aggregate with lactic acid (common cover materials like straw can increase emissions of methane and nitrous oxide), preferably at a temperature below 15 °C (an experiment conducted in a commercial piggery, emptied of pigs showed that increasing the temperature of slurry from 15 to 20 °C results in doubling of CO 2 emissions), and mixing the slurry just before emptying the tank [20,24,25,29,33]. Berg et al [24] showed that combinations of cover materials (perlite, lightweight expanded clay aggregate or chopped straw) and acidification (using lactic acid) of pig slurry reduces CH 4 and N 2 O emissions during storage effectively [24].…”
Section: Emission Of Greenhouse Gases From Pig Slurry and Methods Of mentioning
confidence: 99%
“…Operations which reduce GHG emissions from pig slurry during its storage and applying into the soil are: acidification, separation into solid and liquid fractions (however, some authors observed increased emissions after separation of pig slurry into fractions), anaerobic digestion (promotes anoxic processes and biogas (rich in CO 2 and CH 4 ) production, which can be used for electricity and heat production) and aeration (pig slurry aeration lowers CH 4 and CO 2 emissions while increasing N 2 O emission; however, the total effect of GHG emissions is lower in comparison to emissions from pig slurry not subjected to aeration) [8,16,20,25,29,[32][33][34][35]. Bertora et al [35] concluded that the separation of pig slurry reduces the N 2 O emissions with respect to the non-separated slurry.…”
Section: Emission Of Greenhouse Gases From Pig Slurry and Methods Of mentioning
confidence: 99%
See 2 more Smart Citations